2019
DOI: 10.22159/ajpcr.2019.v12i3.30395
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Antibacterial Activity of Medicinal Plants in the Central North of Morocco: A Possible Source of Alternative Drugs Against Methicillin-Resistant Staphylococcus Aureus

Abstract: Objective: The present study aims the investigation of the antimicrobial potential of medicinal plants selected in the central north of Morocco against methicillin-resistant Staphylococcus aureus and Staphylococcus epidermidis strain often involved in dermatitis. Methods: Structured interviews were carried out among 91 herbalists and traditional healers through a specific information questionnaire, the in vitro susceptibility of Staphylococcus strains award ethanol extracts was evaluated using the well-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…In the study area, the most used parts of plants were leaves. Our results are similar with several studies which clearly demonstrated that the leaves were the most used by population 71,37 . The use of leaves can be explained could be explained by the abundance of phytochemical compounds responsible for the plant's biological properties 72 .…”
Section: Fig 4: Parts Of Plants Used Fig 5: Mode Of Preparation Of supporting
confidence: 93%
See 1 more Smart Citation
“…In the study area, the most used parts of plants were leaves. Our results are similar with several studies which clearly demonstrated that the leaves were the most used by population 71,37 . The use of leaves can be explained could be explained by the abundance of phytochemical compounds responsible for the plant's biological properties 72 .…”
Section: Fig 4: Parts Of Plants Used Fig 5: Mode Of Preparation Of supporting
confidence: 93%
“…Moreover, Lamiaceae and Asteraceae family's were also the most reported in Moroccan ethno-pharmacological studies 33,34 . Indeed, the Lamiaceae are used by the Moroccan population for treatment of various pathologies 36,37 . The chemical composition of Lamiaceae is endowed with antimicrobial activity 38, 39 .…”
Section: Fig 4: Parts Of Plants Used Fig 5: Mode Of Preparation Of mentioning
confidence: 99%
“…The five studied plants were selected from an ethnopharmacological study undertaken in Sefrou city (Center of Morocco) [19]. Based on the calculated frequency index, the five plants were the most cited by herbalists to cure skin infections, and the used parts were also prescribed by herbalists (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…More recently, Zeouk et al (2019) investigated the antimicrobial activity of Rhamnus alaternus [ 127 ] against various staphylococcal strains. After the ethanolic maceration, leaves’ extracts were investigated in a range of concentration varying between 0.5 and 16 mg/mL; with other antibiotics in the strain’s antibiogram, the ampicillin (100 µg/mL) and distillated water were respectively used as positive and negative control.…”
Section: Biological Propertiesmentioning
confidence: 99%